Perancangan Sistem Monitoring Pengukuran Kinerja Produksi Gula Menggunakan Model BSC-SCOR Pada Pabrik Gula - Naufal Hesantra Harijadi; Nova Indah Saragih; Nia Novitasari (Universitas Batanghari Jambi, 2022)
Poor supply chain management can cause operational costs to swell, which consumes business funds while slowing down the delivery process to customers. The Redjosari Sugar Factory currently has a decline in the percentage level of productivity and is still below the predetermined production target. This is because it has not been able to identify and monitor its success or failure and has not decided for performance measurement standards. For this reason, it is necessary to measure the performance of the factory. This study aims to determine the KPI criteria for measuring performance in production activities and to design a monitoring system. The research was conducted using the BSC and SCOR methods. Tools are needed to identify Key Performance Indicators (KPI) in its application and then combined with the AHP method. Furthermore, the monitoring system design and Kendall Tau test were carried out. The study results obtained 11 KPIs for measuring supply chain performance in the production activities of the Redjosari Sugar Factory. In addition, the performance measurement system designed in this study is a dashboard monitoring system based on the Microsoft Excel application. The dashboard monitoring system that has been created can be used to monitor the performance of supply chain activities through the level of production activity at each KPI and monitor the overall progress of the performance results of each perspective on the BSC model. Based on the results of the Kendall Tau correlation analysis between the monitoring system and the effectiveness of the production process, it was found that there was a relationship between the two variables and had a strong relationship. The results of this study can be used as a reference for improving performance at the Redjosari Sugar Factory.